Is it justifiable to assert that clinical lycanthropy may be correlated to porphyria cutanea tarda? - Lorenzo Martini (Our Dermatology Online, 2017)
Scope of this study is to demonstrate an old theory expressed in 1963, when Illis (Guy's Hospital in London) established a correlation between the clinical lycanthropy and congenital porphyria cutanea tarda. We had the fortune to live in a village where they say a lycanthrope lives too and is accustomed to hid himself at home for the 3 days when on the full moon, when he becomes (and behaves as) a werewolf. Werewolves like to walk around before dawn craving for water and since We love to walk very early in the morning (as philosopher Emanuel Kant used to do), We have had this chance to encounter this mysterious man, who is a normal man with a regular lifestyle according to lunar cycle. He presents a very pale face with scares and blisters and generally when somebody asks him about this cutaneous manifestations he says he detests sun and light and his skin reacts by this way. We attempted to treat this individual by a pomade containing rutin, diosmin,Centella asiatica,niacinamide and escin. Results are encouraging as well.